Pengembangan Aplikasi MySaku Menggunakan Metode Waterfall - Akmal Hidayat; Nur Qirani Ridhaihi; M Fiqral Ash Shiddiq; Febrianti Tandi Ra'pak; Andi Ashilla Khaerunnisa (Indonesian Technology and Education Journal, 2023)
Students need to record in detail all the expenses they incur. It is important to work out routine expenses, such as monthly bills, rent, or food, from unscheduled expenses, such as health care costs, urgent needs, or unplanned purchases. By differentiating these expenses, students can have a better understanding of how their expenses are distributed and where they can reduce costs if needed. MySaku is the right solution which is an application that makes it easy for users to record expenses and settlements efficiently. By using this application, users can easily record their every financial transaction, be it daily expenses, bills, or additional income. This study uses the R&D method using the waterfall model.